2020
DOI: 10.1186/s12889-020-8408-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of life expectancy and clustering of provinces to improve life expectancy: an ecological study in Indonesia

Abstract: Background: Life expectancy acts as a population measure of the performance of healthcare systems. Regional disparities on life expectancy in Indonesia has been persisted and become a public health policy challenge. A systematic clustering of provinces can be a valuable alternative for organizing cooperation that aimed to increase life expectancy and reduce disparities. This study aimed to identify determinants of life expectancy and designate clusters of Indonesian provinces with similar characteristics. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…In addition to the three methods above, Paramita used a great likelihood estimation model to examine the determinants of life expectancy in Indonesia [47]. Bushnik constructed a bootstrap model to explain the persistence of the life expectancy gap in Canada [48].…”
Section: Methods Reviewmentioning
confidence: 99%
“…In addition to the three methods above, Paramita used a great likelihood estimation model to examine the determinants of life expectancy in Indonesia [47]. Bushnik constructed a bootstrap model to explain the persistence of the life expectancy gap in Canada [48].…”
Section: Methods Reviewmentioning
confidence: 99%
“…Use of clustering analysis to find meaningful groups with attributes that explain mental health outcomes is a recent innovation. Prior studies have used clustering analysis to group Indonesian providences with area-based health profiles ( Paramita et al, 2020 ), and to identify meaningful patients’ groups with health conditions such as end-stage chronic diseases ( Finamore et al, 2021 ) and liver transplant ( Pruinelli et al, 2016 ). Also, this method allowed to create the independent variable of neighborhood attributes to examine the relationships between availability or accessibility of neighborhood resources and mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Raghupathi and Raghupathi ( 38 ) investigated the interaction between education and health in 26 OECD states for the 1995–2015 period and concluded that higher education level positively affected public health and life expectancy. Paramita et al ( 39 ) explored the determinants of life expectancy in 34 provinces of Indonesia via cluster analysis based on structural equation modeling and found a positive effect of average schooling years on life expectancy.…”
Section: Literature Reviewmentioning
confidence: 99%